The Effect of Cartoon Film Toward Students’ Reading Comprehension in Narrative Text at the 9th Grade of SMPN 2 Rao Selatan - Wela, Raima; Eliza, Eliza; Dewi, Merry Prima; Syahrul, Syahrul (ALSYS, 2023)
This research was motivated by several problems of students at the 9th grade of SMPN 2 Rao Selatan related to students’ reading comprehension in narrative text. The problems of this research were students felt difficult to determine the main idea in narrative text. Students were low enthusiastic in learning. This research aimed to know whether there was significant effect of using cartoon film on students’ reading comprehension in narrative text. The researcher used a pre experimental research with one group pretest posttest design. The population of this research was the 9th grade students of SMPN 2 Rao Selatan consist of 2 classes, the sample was in class IX.1 which was taken by using purposive sampling technique. The data was analyzed by using liliefors test to test the normality and homogeneity data. Whereas, the hypothesis the researcher used t test, then the researcher consulted the result with the degree table (a) = 0.05. The research findings showed that the reading comprehension in narrative text of students at the 9th grade of SMPN 2 Rao Selatan had poor score in pretest which mean score 51.40. After treatment, their reading comprehension increased significantly which mean score 72.00. The result of the t-obtained =9.726 > t-table=2.093 with degree freedom (df) =19 with 0.05/2=0.025. Meanwhile, the Sig (2-tailed) was 0.000 < 0.005. So, the alternative hypothesis (Ha) was accepted that there was significant effect of using cartoon film. It was proven that using cartoon film can help to improve students’ reading comprehension in narrative text.